WingBank: A Wing Image Database of Mosquitoes - Virginio, Flávia; Domingues, Victor; da Silva, Letícia Cecília Gomes; Andrade, Lucas; Braghetto, Kelly Rosa; Suesdek, Lincoln (Frontiers in Ecology and Evolution, 2021)
Mosquito-borne diseases affect millions of people and cause thousands of deaths yearly. Vaccines have been hitherto insufficient to mitigate them, which makes mosquito control the most viable approach. But vector control depends on correct species identification and geographical assignment, and the taxonomic characters of mosquitoes are often inconspicuous to non-taxonomists, which are restricted to a life stage and/or even damaged. Thus, geometric morphometry, a low cost and precise technique that has proven to be efficient for identifying subtle morphological dissimilarities, may contribute to the resolution of these types of problems. We have been applying this technique for more than 10 years and have accumulated thousands of wing images with their metadata. Therefore, the aims of this work were to develop a prototype of a platform for the storage of biological data related to wing morphometry, by means of a relational database and a web system named "WingBank". In order to build the WingBank prototype, a multidisciplinary team performed a gathering of requirements, modelled and designed the relational database, and implemented a web platform. WingBank was designed to enforce data completeness, to ease data query, to leverage meta-studies, and to support applications of automatic identification of mosquitoes. Currently, the database of the WingBank contains data referring to 77 species belonging to 15 genera of Culicidae. From the 13,287 wing records currently catalogued in the database, 2,138 were already made available for use by third parties. As far as we know, this is the largest database of Culicidae wings of the world.